Pengaruh Kelereng Sebagai Substitusi Agregat Kasar Pada Campuran Beton Mutu Normal - Dominggus Paerunan; Jonie Tanijaya; Olan Jujun Sanggaria (Paulus Civil Engineering Journal, 2023)
Various tests have been carried out in the field of concrete materials as an effort to improve the quality of concrete. One of the many efforts made is the use of substitute materials in concrete mixtures. This study used marbles as a substitute for one of the concrete mixture materials, namely gravel with a plan quality of 25 Mpa. The variation of this test mixture is 0%, 5%, 10% and 15% with the SNI 03-2834-2000 Mix Design method. Based on the results of the study, the average test results for compressive strength aged 28 days (25.428), (23.399), (22.301), (21.365) with MPa units. For the tensile strength test aged 28 days, the average test results were obtained (2.734), (2.310), (1.980), (1.886) and (2.921), (2.619), (2.594), and (2.418) with MPa units for the average flexural strength test results.